2018
DOI: 10.3126/banko.v27i3.20544
|View full text |Cite
|
Sign up to set email alerts
|

Modeling taper and volume of Sal (Shorea robusta Gaertn. f.) trees in the western Terai region of Nepal

Abstract: Volume and taper equations are used for estimating timber volume and biomass of a tree. Despite their usefulness, precise and site specific equations are still lacking for commercially important tree species in Nepal. The study was carried out at Chandak Chatiya Mahila Community Forest in Bardia district and Lumbini Collaborative Forest of Saljhandi in Rupandehi district in western Terai of Nepal. A destructive sampling method was used and selected fifteen Sal trees (Shorea robusta Gaertn. f.) from Saljhandi (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Taper functions for tree species of Nepal are limited. Only the taper function developed by Silwal et al (2018) is available for S. robusta which used 33 trees from two different sites of the Terai region. Our study has used a relatively larger number of sample trees (n = 54).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Taper functions for tree species of Nepal are limited. Only the taper function developed by Silwal et al (2018) is available for S. robusta which used 33 trees from two different sites of the Terai region. Our study has used a relatively larger number of sample trees (n = 54).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have also reported that better performance of segmented taper functions over variable exponent taper functions (Crecente-Campo et al 2009;Özçelik and Crecente-Campo 2016;Shahzad et al 2021). Several studies have been carried out on tree tapers in different areas of the world (Candy 1989;Fang and Bailey 1999;Kozak 2004;Sharma and Patron 2009;Arias-Rodil et al 2015;Poudel et al 2018;Silwal et al 2018;Alkan and Özçelik 2020;Shahzad et al2021)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…О. В. Поляков описав твірну стовбура рядом Фур'є за непарними багаточленами Чебишева першого роду (Polyakov, 2008), а А. З. Швиденко застосував показникову функцію, яка монотонно спадає й не має точок перегину. У закордонних працях опрацьовано чимало схожих моделей, які успішно апробовані на практиці (Fonweban et al, 2012;Rojo et al, 2005;Socha, 2002;Silwal et al, 2018).…”
unclassified